Factors influencing forward extraction of jacalin from aqueous phase into anionic reverse micelles - Sharifah Fathiyah, Sy Mohamad; Farhan, Mohd Said; Mimi Sakinah, A. M.; Shahril, Mohamad (2018)
Background: This study deals with the extraction of jacalin from crude extract of jackfruit seed using anionic surfactant based reverse micellar system, dioctyl sulfosuccinate sodium salt (AOT) in isooctane. The effect of AOT concentration, NaCl concentration and aqueous phase pH on the forward extraction efficiency of jacalin was evaluated using one factor at a time experiments (OFAT). Results: AOT concentration, NaCl concentration and aqueous phase pH were found to have different effects on the removal of jacalin from the aqueous phase into the AOT reverse micelles. A maximum forward extraction efficiency of 78% was achieved after the mixture was stirred for 15 min using 10 mM AOT at pH 5 aqueous phase containing 0.1 M NaCl. Conclusion: The findings demonstrated AOT reverse micellar system as a promising and effective method to extract and purify jacalin from crude protein mixture.